Risk Factors and Predictive Model of Diarrhea in Kupang - Irfan, Irfan - (Jurnal Kesehatan Masyarakat, 2016)
Diarrhea is still endemic in NTT province and in Kupang City. The disease also includes as one of the 10 major diseases in Kupang City. Diarrhea prevention will work more effectively if it is conducted based on the knowledge of risk factors for diarrhea. The study aims at analyzing the risk factors of diarrhea and predictive models of diarrhea incidence in Kupang. The observational analytic research used case control design with case samples consisted of 62 patients with diarrhea in June 2015 taken by random sampling and control samples consisted of 62 children who were not listed as diarrhea patients in June 2015. The data was collected through interviews and observation. Bivariate and multivariate analyses were performed using logistic regression. Four variables that significant are age of stop getting breast milk (ASI) (OR 5.673), latrine type (OR 4.527), children age (OR 1.460) and number of family members (OR 0.484). The regression model resulted in the study is Å¶ = -0.630 + 1.736 age of stop drinking breast milk + 1.510 latrine type + 0.379 children age - 0.726 number of family members.